2020
DOI: 10.1152/ajpcell.00091.2019
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Wnt6 mediates diabetes-associated centrosome amplification via its receptor FZD4

Abstract: We recently published that type 2 diabetes promotes cell centrosome amplification via upregulation of Rho-associated protein kinase 1 (ROCK1) and 14-3-3 protein-σ (14-3-3σ). This study further investigates the molecular mechanisms underlying diabetes-associated centrosome amplification. We found that treatment of cells with high glucose, insulin, and palmitic acid levels increased the intracellular and extracellular protein levels of Wingless-type MMTV integration site family member 6 (Wnt6) as well as the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…The expression of WNT6 gene was decreased after overexpression of NFE2L1 or NFE2L1 ΔC . However, FZD4 and FZD8, genes encoding WNT6's receptors [36], were increased ( Fig. 5F).…”
Section: Nfe2l1 Inhibits the Wnt/β-catenin Signaling Pathwaymentioning
confidence: 98%
“…The expression of WNT6 gene was decreased after overexpression of NFE2L1 or NFE2L1 ΔC . However, FZD4 and FZD8, genes encoding WNT6's receptors [36], were increased ( Fig. 5F).…”
Section: Nfe2l1 Inhibits the Wnt/β-catenin Signaling Pathwaymentioning
confidence: 98%
“…The activation of ATF3/NFAT axis causes podocyte injury during the development of DN, and ATF3 is increased in glomeruli from proteinuric patients with DP, and Wnt6 is up‐regulated in ATF3‐overexpressed podocytes and identified as a target of this axis, indicating Wnt6 may aggravate podocyte injury and loss 104 . Furthermore, the activation of Wnt6/β‐catenin pathway in diabetic context establishes a pathological link between T2DM and cancer due to the inducing effect of this signalling on the amplification of centrosome, a symbolic event associated with high‐grade tumours and poor prognosis 105 . Thus, further studies are needed to explore the role of Wnt6 in the development of T2DM and related complications.…”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 99%
“… 104 Furthermore, the activation of Wnt6/β‐catenin pathway in diabetic context establishes a pathological link between T2DM and cancer due to the inducing effect of this signalling on the amplification of centrosome, a symbolic event associated with high‐grade tumours and poor prognosis. 105 Thus, further studies are needed to explore the role of Wnt6 in the development of T2DM and related complications.…”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 99%
“…In vitro experiments have identified that the pathophysiological factors in type 2 diabetes, including high glucose, insulin and free fatty acids (such as palmitic acid), are potent inducers, and that the centrosomal translocation of Rho-associated protein kinase 1 (ROCK1) is a signal for diabetes-associated centrosome amplification (6). Moreover, inhibition of ROCK1 partially attenuated centrosome amplification (6,20). These results suggest that centrosome amplification may be a candidate mechanism for the association between type 2 diabetes and cancer development, and that type 2 diabetes may present a natural model to investigate the roles of centrosome amplification in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the ROCK1 genotype was found to be associated with colon cancer in men (25), and is a candidate prognostic marker for vulvar cancer (26). Our previous studies revealed that ROCK1 signaling promotes diabetes-associated centrosome amplification (6,20). However, inhibiting ROCK1 only partially suppresses centrosome amplification, indicating that other factors are involved.…”
Section: Introductionmentioning
confidence: 99%